The Mediating Effect Of Internationalisation On Firm Performance Among E&E Manufacturing Sme’s - Maniam, Gayathiri (2019)
E&E Manufacturing industry is considered as a value-added business to Malaysian economy. This research addresses new theoretical framework to describe the relationship between competitive advantages (innovation differentiation, marketing differentiation, low cost leadership, quality differentiation and service differentiation), management attitudes, and internationalisation as the mediating factor towards firm performance for the E&E manufacturing SME’s. The conceptual framework, helps firms to determine the factors that contribute to the success of firm performance and effectiveness of internationalisation to support E&E manufacturing. The results indicate that E&E manufacturing SME’s firm performance are positively related to competitive advantages (marketing differentiation, low cost leadership). With the moderating effect of internationalisation, shows significant positive relationship between competitive advantages (innovation differentiation, marketing differentiation and low cost leadership) and also management attitudes. Internationalisation is important to strengthen E&E manufacturing SME’s firm performance, by helping to improve firm’s competitive advantages and management attitudes. Internationalisation helps E&E firms to expand globally by creating a platform and provide sufficient source to expand the firms’ competitive advantages (innovation differentiation, marketing differentiation and low cost leadership) and also management attitudes. The research model is tested using the Partial Least Squad (PLS) technique. The quantitative method was employed in completing this thesis.